Peningkatan Hasil Belajar Pada Mata Pelajaran Akidah Akhlak Melalui Penerapan Value Clarification Technique (VCT) Di Kelas III MIN 3 Tangerang - Siti Khoeriyah; Miftakhul Arif (Lembaga Pengembangan Kinerja Dosen, 2024)
Education in Indonesia is currently experiencing a lot of changes, especially in the field of technology. With the rapid development of technology and increasingly sophisticated makes learning more interesting. With the advancement in technology, it is expected that students will be more enthusiastic in learning at school. One of them is with a learning model that can be applied by students. The Value Clarification Technique (VCT) learning model is a learning model that aims to help students find and find values that are considered good to be applied in everyday life by analyzing the values that have been embedded in students. The characteristic of this learning model is in the form of attitudes where the process of instilling these values is carried out by analyzing existing values and aligning them with the values to be instilled. The purpose of this study is to determine the extent to which the use of the Value Clarification Technology (VCT) learning model can improve the learning outcomes of Akidah Akhlak students in grade III MIN 3 Tangerang. The aim of this research is to determine the extent to which the use of the Value Clarification Technique (VCT) learning model can improve the learning outcomes of students' Aqidah Akhlak in class III MIN 3 Tangerang.The author conducted field research, using qualitative methods. The data source in this research uses data collection techniques through observation, interviews and documentation Based on the results of the observation analysis, student learning results and discussion, it can be concluded that the use of the Value Clarification Technique (VCT) method can improve Aqidah Akhlak learning outcomes for class III students at MIN 3 Tangerang. This success is due to the use of the Value Clarification Technique (VCT) learning model which is The previous teacher's activities were classified as